Explaining Role of Cadre Understanding and Values of Political Parties towards Women’s Legislative Candidacy in Jambi - Yusnaini Yusnaini; Eraskaita Ginting (Jurnal Studi Sosial dan Politik, 2021)
Cadre formation is essential in a political party. The current phenomenon is that many political parties have not been able to carry out the selection and regeneration process as expected, especially for women legislative candidates. In comparison, the quality of cadres in a political party determines the selling power of the social party. This study is essential to do considering that the legislative members who sit as people's representatives in the DPR must carry out their functions as people's representatives in conveying their aspirations and ideas to the government. The Legislature who is elected as the people's representatives in communicating aspirations must be people or cadres who have capability and acceptability. The purpose of this study was to determine the role of regeneration in understanding party values​​. The results of this study can provide recommendations to political parties in selecting and nominating their members. The qualitative research method with a phenomenological study approach and systems theory in organizational communication is considered relevant for analyzing existing cases. Data was collected through interviews with party officials, women legislative members, female legislative candidates in Jambi city, political observers or academics. The results showed that the higher the quality of the cadre system carried out by a political party, the better the quality of the party’s cadres when occupying political positions both internally and externally.